2003
DOI: 10.1104/pp.102.019562
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Differential Expression of Two Thioredoxin h Isoforms in Germinating Seeds from Pea

Abstract: The NADPH/NADP-thioredoxin (Trx) reductase (NTR)/Trx system (NTS) is a redox system that plays a posttranslational regulatory role by reducing protein targets involved in crucial cellular processes in microorganisms and animals. In plants, the system includes several h type Trx isoforms and has been shown to intervene in reserve mobilization during early seedling growth of cereals. To determine whether NTS was operational during germination of legume seeds and which Trx h isoforms could be implicated, Trx h is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 52 publications
1
50
1
Order By: Relevance
“…In addition, three-dimensional models for both deduced sequences, based on resolved h-type TRXs (Coudevylle et al, 2005), fit well to the classical TRX folding (data not shown). Compared to other TRXs from pea, we found a high similarity of both PsTRXh1 and PsTRXh2 with PsTRXh3 (64% and 72% identity, respectively); however, they both share less than 41% identity with PsTRXh4, the latest cytosolic isoform isolated up to now (Montrichard et al, 2003). Contrary to chloroplastic TRXs, PsTRXh1 and PsTRXh2 do not contain any transit peptide.…”
Section: Pstrxh1 and Pstrxh2mentioning
confidence: 72%
See 2 more Smart Citations
“…In addition, three-dimensional models for both deduced sequences, based on resolved h-type TRXs (Coudevylle et al, 2005), fit well to the classical TRX folding (data not shown). Compared to other TRXs from pea, we found a high similarity of both PsTRXh1 and PsTRXh2 with PsTRXh3 (64% and 72% identity, respectively); however, they both share less than 41% identity with PsTRXh4, the latest cytosolic isoform isolated up to now (Montrichard et al, 2003). Contrary to chloroplastic TRXs, PsTRXh1 and PsTRXh2 do not contain any transit peptide.…”
Section: Pstrxh1 and Pstrxh2mentioning
confidence: 72%
“…This pattern of protein accumulation was not consistent with PsTRXh2 mRNA accumulation. It is likely that these levels mostly correspond to cross recognition of other abundant isoforms such as PsTRXh3, for which similar patterns were previously reported (Montrichard et al, 2003). Therefore, PsTRXh2 accumulation could not be further investigated.…”
Section: Pstrxh1 Pstrxh2 Mrnas and Derived Proteins Are Differentlymentioning
confidence: 93%
See 1 more Smart Citation
“…The pea cytosolic system consists of Trx h and homodimeric NTR (Montrichard et al 2003), and Trx f and a heterodimeric ferredoxin-dependent Trx reductase for the chloroplastic Trx system (Cain et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Subsequent events, including the mobilization of the major reserves, are associated with the growth of the seedling (Bewley 1997). A potential role of Trxs in redox status of storage proteins and proteolysis during germination has been already suggested (Lozano et al 1996;Montrichard et al 2003;Alkhalfioui et al 2007). They appear to play a role in the reduction of critical disulfide bonds of proteins (Kobrehel et al 1992;Besse et al 1996;Lozano et al 1996;Schu¨rmann and Jacquot 2000).…”
Section: Introductionmentioning
confidence: 99%